Sliding mode control design for the benchmark problem in real-time hybrid simulation. (April 2021) - Li, Hongwei; Maghareh, Amin; Montoya, Herta; Condori Uribe, Johnny Wilfredo; Dyke, Shirley J.; Xu, Zhaodong
Highlights: The present work demonstrates an RTHS control strategy that a relatively lower-order control plant with uncertainties is able to replace a higher-order control plant. A sliding mode controller is formed for a benchmark problem using this control strategy. Simulation results show extremely high performance and robustness of the sliding mode controller designed for the benchmark problem. Abstract: Real-time hybrid simulation (RTHS) is a novel cyber-physical testing technique for investigating especially large or complicated structural systems. Controllers are required to compensate for the dynamics of transfer systems that emulate the interactions between the physical and numerical substructures. Thus, both the stability and accuracy of RTHS testing highly depend on the effectiveness of the control strategy. This paper proposes a robust sliding mode controller (SMC) as a transfer system control strategy in RTHS. A design procedure of the SMC control strategy is presented. The benchmark problem on RTHS control is utilized for demonstration and validation of SMC for this class of problems. Virtual RTHS results show that the SMC strategy significantly improves the performance and robustness of RTHS testing.